Analisis Faktor-Faktor yang Memengaruhi Implementasi Bimbingan Perkawinan Calon Pengantin di KUA Kecamatan Sukajadi Kota Bandung - Putranto Bifadlillah Bifadlillah; Ilham Mujahid; Fahmi Fatwa Rosyadi Satria Hamdani (UNISBA Press, 2023)
Abstract. Deviations from the rules for registration of marriage will, which is no later than 10 working days before the wedding, will affect the implementation of the Marriage Guidance for the Bride and Groom (Bimwin Catin). Then, the use of Youtube media as an optimization effort from Bimwin Catin. This study examines the adverse factors in the implementation of Bimwin Catin in KUA Sukajadi District. The research method used is qualitative with a normative juridical approach. Data collection by observation methods, interviews and documentation. Data analysis techniques use data reduction, data presentation and data verification. The results showed that: The implementation of Bimwin Catin in KUA Sukajadi District, Bandung City is not completely perfect as evidenced by, First, related to funds that are sometimes lacking. Second, the various methods provided have not been used as a means of the Binwin Catin process like the virtual method. Third, as well as the involvement of participants who have not been fully effective so that it affects its implementation. Abstrak. Penyimpangan pada peraturan pendaftaran kehendak nikah yaitu paling lambat 10 hari kerja sebelum dilaksanakan pernikahan, akan berimbas pada pelaksanaan Bimbingan Perkawinan Calon Pengantin (Bimwin Catin), serta pemanfaatan media Youtube sebagai upaya optimalisasi dari Bimwin Catin. Penelitian ini mengkaji faktor-faktor yang memengarugi dalam pelaksanaan Bimwin Catin di KUA Kecamatan Sukajadi. Metode penelitian yang digunakan yaitu kualitatif dengan pendekatan yuridis normatif. Pengumpulan data dengan metode obsevasi, wawancara dan dokumentasi. Teknik analisis data menggunakan reduksi data, penyajian data dan verifikasi data. Hasil penelitian menunjukkan bahwa: Pelaksanaan Bimwin Catin di KUA Kecamatan Sukajadi Kota Bandung yang belum sepenuhnya sempurna yang dibuktikan dengan, Pertama, terkait dana yang terkadang kurang. Kedua, berbagai metode yang disediakan belum dijadikan sarana proses Binwin Catin seperti metode virtual. Ketiga, serta keterlibatan peserta yang belum sepenuhnya efektif sehingga memengaruhi pelaksanaannya.